Molecular characterization and varietal identification for multiple abiotic stress tolerance in rice (Oryza sativa L.) - Ali, Alif; R, Beena; Naga Manikanta, Chennamsetti Lakshmi; Alex, Swapna; KB, Soni; MM, Viji (ORYZA-An International Journal of Rice, 2022)
Coexistence of two or more abiotic stresses is common in most of the rainfed lowland and upland rice growing areas of India and worldwide. Rice production under these conditions is not sustainable. Identification and development of multiple abiotic stress tolerant rice varieties are to be addressed. Here we tried to identify multiple abiotic stress tolerant varieties from a collection of earlier identified varieties for single stress and validated the known SSR markers for stress tolerance. Twenty rice genotypes were evaluated for individual abiotic stress such as drought, salinity and temperature initially and the tolerant three genotypes in each case were further evaluated for combination of stresses various physio-morphological and biochemical parameters were recorded. Among the genotypes evaluated for combination of stresses, PTB-7 was found to be tolerant for drought and salinity, Nagina-22 was tolerant against high temperature and salinity. However, the seeds did not germinate in the presence of all three stresses simultaneously. Twenty rice varieties viz., Chomala, MO-16, PTB-35, PTB-60, PTB-39, PTB-55, PTB-30, PTB-7, CRdhan307, Apo, Vyttila-3, Vyttila-4, Vyttila-5, Vyttila-6, Vyttila-7, Vyttila-8, Vyttila-9, Vyttila-10, Nagina-22 and NL-44 were further investigated using microsatellite markers to confirm the genotypic level of tolerance to combination of abiotic stresses. Rice genotypes were screened using 30 reported simple sequence repeat (SSR) markers that are linked to drought, salinity and temperature. Molecular marker analysis of rice genotypes also confirmed that RM8904 and RM1287 were associated with salinity tolerance, RM2612, RM6100 and RM5749 were linked to high temperature tolerant trait.Â  Population analysis also revealed that there is five subpopulation among rice genotypes.